DNA damage response and GATA4 signaling in cellular senescence and aging-related pathology - Xiong, Hao; Hua, Fuzhou; Dong, Yao; Lin, Yue; Ying, Jun; Liu, Jie; Wang, Xifeng; Zhang, Lieliang; Zhang, Jing (Frontiers in Aging Neuroscience, 2022)
Aging is the continuous degradation of biological function and structure with time, and cellular senescence lies at its core. DNA damage response (DDR) can activate Ataxia telangiectasia mutated serine/threonine kinase (ATM) and Rad3-related serine/threonine kinase (ATR), after which p53 activates p21, stopping the cell cycle and inducing cell senescence. GATA4 is a transcription factor that plays an important role in the development of many organs, such as the heart, testis, ovary, foregut, liver, and ventral pancreas. Studies have shown that GATA4 can also contribute to the DDR, leading to aging. Consistently, there is also evidence that the GATA4 signaling pathway is associated with aging related-diseases, including atherosclerosis and heart failure. This paper reviews the relationship between GATA4. DDR and cellular senescence, as well as its effect on aging-related diseases.